The Comparison of Students’ Reading Comprehension Between Natural Science and Social Science Students at State Senior High School 1 Tapung - darliza listari; R. Roswati (Indonesian Journal of Integrated English Language Teaching, 2019)
The purpose of this study is to know the comparison of students’ reading comprehension in descriptive text between natural science and social science students at State senior High School 1 Tapung. The total population of this research was 210 students which consisted of seven classes, the researchers took 20% of the population as the sample by stratified random sampling. The design of this research was quanitative used comparative research. In collecting the data, the researchers distributed a reding comprehension test based on the indicators. After analyzing the data, the researchers found that that there was a significant difference of reading comprehension between natural science and social science students on reading descriptive text comprehension at the tenth grade of State Senior High School 1 Tapung. It was considered by t obtained = 3.329 that was higher than t-table either at 5% = 2.021 or 1% = 2.704. It means that Ha was accepted and Ho was rejected. From the research finding, it showed that there was a significant difference in reading comprehension of descriptive text between natural science and social science students at the tenth grade of State Senior High School 1 Tapung.